PENGARUH EFISIENSI PEMBASAHAN KATALIS TERHADAP KONVERSI SO2 DALAM REAKTOR TRICKLE BED - -, Mahfud; Husodo, F.; Irawan, C. (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2007)
Trickle-bed reactors, in which gas and liquid flow concurrently downward, is po-tentially useful for oxidation catalytic of SO2 with activated carbon as catalyst. To predict trickle bed reactor performance and model its behaviour, it is necessary to know what fraction of the catalyst is effectively wetted by the liquid phase. It is known that contacting efficiency can have a significant effect on the catalyst effectiveness factor for partially wetted catalyst particles. The dynamics tracer method with pulse input is an efficient me-thod for determination of liquid-solid contacting. Axial dispersion, residence time distributi-on also can be evaluated with this method. The aims of this research are to study the in-fluence of catalyst wetting efficiency in trickle bed reactor on reaction catalytic oxidation SO2. The experimental apparatus is a trickle bed reactor with 4.8 10-2 m column diameter and 35 10-2 m length. The column is packed with activated carbon. The operating conditi-ons of reactor are liquid flow rate 12.2 – 23.7 10-6 m3/s, gas flow rate 133 – 243.4 10-6 m3/s, atmospheric pressure, and room temperature. The NaCl solution is used as a tracer with impulse injection mode and a conductometer, which connected to personal compu-ter, detects the outlet tracer concentrations. The results show that the wetting efficiency increases significantly with liquid flow rate, but it slightly increases with gas flow rate. Wetting efficiency is considerably influenced by the form of packing particle and increa-sed with the bed voidage. Catalytic oxidation of SO2 in trickle bed reactor attains steady state condition about no more than 60 minutes. Conversion of reaction increases with li-quid phase rate and the increasing wetting efficiency will increase this conversion.